TACTICS OF TREATMENT FOR POSTTRAUMATIC SOFT TISSUE DEFECTS OF EXTREMITIES - E. Y. Shibayev; P. A. Ivanov; A. V. Nevedrov; M. P. Lazarev; A. P. Vlasov; L. L. Tsoglin; A. L. Rybinskaya (Неотложная медицинская помощь, 2018)
Background Due to the non-decreasing incidence of such injuries, prolonged treatment and high incidence of complications, treatment of posttraumatic soft tissue defects of extremities is an actual problem within traumatology and plastic and reconstructive surgery. Aim of study Development of tactics for the treatment of posttraumatic soft tissue defects of extremities with the use of vascularized tissues (flaps) and evaluation of its results. Materials and methods: 118 patients with posttraumatic soft tissue defects of extremities were included into the study. Patients were divided into 2 groups. In the comparison group (49 patients), the traditional management for posttraumatic defects was performed: local treatment of the wound followed by autodermoplasty. In the second group (study group), the developed procedure of cover tissues restoration using vascularized tissue complexes (69 patients) was applied. Results The developed treatment reduced the incidence of deep wound infection by 13.6%, necrosis of naked functional structures by 36.3%, chronic osteomyelitis by 17% and contraction of adjacent joints by 18.2%. At the same time, we noted a decrease in the duration of inpatient treatment by 14.7 days in patients with posttraumatic soft tissue defects of extremities. Conclusion The developed tactics of cover tissues restoration using vascularized tissue complexes reduced the incidence of complications and improved the functional results of treatment in patients with posttraumatic soft tissue defects of extremities.